2023
DOI: 10.1051/epjam/2022018
|View full text |Cite
|
Sign up to set email alerts
|

Safe energy-storage mechanical metamaterials via architecture design

Abstract: Mechanical and functional properties of metamaterials could be simultaneously manipulated via their architectures. This study proposes multifunctional metamaterials possessing both load-bearing capacity and energy storage capability, comprising multi-phase lattice metamaterial and cylindrical battery cells. Defect phase are incorporated into the metamaterials, which are then printed with stainless steel powder. The printed metamaterials are assembled with battery cells and compressed. Experimental results reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…J You et al [36] demonstrated how to design an energy-storage metamaterial with enhanced mechanical properties and battery safety simultaneously. Mechanical properties of MM could be simultaneously manipulated via their architectures.…”
Section: Energy Storagementioning
confidence: 99%
“…J You et al [36] demonstrated how to design an energy-storage metamaterial with enhanced mechanical properties and battery safety simultaneously. Mechanical properties of MM could be simultaneously manipulated via their architectures.…”
Section: Energy Storagementioning
confidence: 99%
“…ES schemes involve: Mechanical ES: This includes ES in the form of kinetic, potential, or compression energy. The most frequently utilized schemes for ES as mechanical energy are flywheels and hydroelectric pump storage [ 4 ]. Other mechanical ES schemes exist, such as springs, compressed air, hydraulic accumulators, and gravitational potential.…”
Section: Introductionmentioning
confidence: 99%